The Meteoritical Bulletin, No. 98, September 2010 - Michael K. WEISBERG; Caroline SMITH; Christopher HERD; Henning HAACK; Akira YAMAGUCHI; Hasnaa CHENNAOUI AOUDJEHANE; Linda WELZENBACH; Jeffrey N. GROSSMAN (Meteoritics & Planetary Science, 2010)
Abstract– This issue of The Meteoritical Bulletin reports information on 1103 meteorites including 281 non‐Antarctic meteorites ( Table 1 ) and 822 Antarctic meteorites ( Table 2 ). Reported in full written descriptions are three falls. Full descriptions are also given for three shergottites, two ungrouped irons, a primitive achondrite, an olivine diogenite, and a lunar meteorite. One iron, Gebel Kamil, was found in and around the Kamil impact crater. Also reported is a new dense collection area in Tunisia. Tables list a wide variety of meteorites including chondrites, ureilites, irons, acapulcoites, and HEDs. Antarctic meteorites reported in this edition include meteorites recovered by ANSMET (US), CHINARE (China), KOREAMET (Korea), and the NIPR (Japan) meteorite recovery programs. List of newly approved, non‐Antarctic meteorties by country. Name Location Date of recovery or purchase( p ) Latitude Longitude Mass (g) Pieces Class Sh a WG b Fa mol % Fs mol % Wo mol % Mag sus log10 9 m 3 kg −1 ) Classifier(s) c Type specimen mass (g) Type specimen location Main mass d Comment Meteorites from Argentina Cruz del Eje Cordoba 18‐May‐1971 30°45′S 64°47′W 14kg 1 Iron, IAB complex A. Ruzicka, M. Hutson, Cascadia ; S. Kissin, LHU 21.4 Cascadia Anon Meteorites from Canada Redwater Alberta 30‐Aug‐2009 53°55.974′N 112°58.620′W 230 2 H4 S2 W5 19.2 ± 1.3 16.2 ± 1.5 1.3 ± 0.3 C. Herd, UAb 40.5 UAb B. Newman Meteorites from Ecuador Daule Guayas 23‐Mar‐2008 1°52′15.2″S 79°57′27.2″W 6580 1 L5 S4 W0 24.5 ± 0.5 20.8 ± 0.5 1.4 ± 0.2 J. Grossman, USGS 20.37 SI Farmer See written description Meteorites from Egypt Gebel Kamil Al Wadi al Jadid, East Uweinat Desert 19‐Feb‐2009 22°01′06″N 26°05′16″E 1600 kg 1000s Iron, ungrouped M. D’Orazio, Luigi Folco 1500 MNA‐SI EGM See written description GSS 030 Al Wadi al Jadid 26‐Dec‐2006 26°22.69′N 26°51.03′E 51.3 1 H6 S2 W3/4 18.5 ± 0.2 16.4 ± 0.2 4.71 L. Ferrière & M. Bourot‐Denise, MNHNP 12.2 MNHNP L. Ferrière GSS 031 Al Wadi al Jadid 30‐Dec‐2006 25°26.17′N 25°29.19′E 62.3 1 H5 S3/4 W2 18.6 ± 0.2 16.6 ± 1.0 5.06 L. Ferrière & M. Bourot 14 MNHNP L. Ferrière GSS 032 Al Wadi al Jadid 31‐Dec‐2006 26°11.20′N 25°27.34′E 8.3 1 Acapulcoite W4 7.5 ± 0.2 8.2 ± 0.2 L. Ferrière & M. Bourot 6.7 MNHNP L. Ferrière Ca‐pyx Fs 3.6 Wo 43.5 ; grain sizes ∼100–300; rare relic chondrules GSS 033 Al Wadi al Jadid 31‐Dec‐2006 26°11.20′N 25°27.34′E 80.1 1 L5 S3/4 W2 24.8 ± 0.4 21.2 ± 0.9 4.34 L. Ferrière & M. Bourot 18.7 MNHNP L. Ferrière GSS 034 Al Wadi al Jadid 31‐Dec‐2006 26°11.20′N 25°27.34′E 7.72 1 L5/6 S5/6 W2 24.4 ± 0.6 20.6 ± 1.0 L. Ferrière & M. Bourot 6.2 MNHNP L. Ferrière GSS 035 Al Wadi al Jadid 2‐Jan‐2007 26°37.00′N 26°11.96′E 40.9 1 H5/6 S3/4 W3/4 19.0 ± 0.1 16.3 ± 0.2 L. Ferrière & M. Bourot 8.9 MNHNP L. Ferrière GSS 036 Al Wadi al Jadid 2‐Jan‐2007 26°37.52′N 26°11.90′E 129 1 H5 S2/3 W4/5 19.1 ± 0.2 16.7 ± 0.4 4.56 L. Ferrière & M. Bourot 21.8 MNHNP L. Ferrière GSS 037 Al Wadi al Jadid 2‐Jan‐2007 26°46.28′N 26°32.57′E 66.9 6 H4 S2/3 W3/4 18.6 ± 0.2 16.4 ± 0.2 4.69 L. Ferrière & M. Bourot 15.3 MNHNP L. Ferrière GSS 038 Al Wadi al Jadid 3‐Jan‐2007 26°49.55′N 27°08.54′E 146 1 H5 S4/5 W2 18.8 ± 0.7 17.1 ± 0.6 4.85 L. Ferrière & M. Bourot 24.5 MNHNP L. Ferrière GSS 039 Al Wadi al Jadid 3‐Jan‐2007 26°49.41′N 27°08.49′E 129 1 H5 S4/5 W3/4 18.8 ± 0.3 16.7 ± 0.3 5.18 L. Ferrière & M. Bourot 25 MNHNP L. Ferrière Meteorites from Libya Ashuwairif 001 Ash Shati’ 15‐Nov‐2008 29°21′34 N 14°15′19″E 14566 3 H4 S2 W3 16 14 A. Bischoff, K. Metzler, J. Roszjar 21.5 IfP IfP Ashuwairif 002 Gharyan 15‐Nov‐2008 29°22′47″N 14°16′11″E 11953 6 L5/6 S4 W2 24 20 A. Bischoff, K. Metzler, J. Roszjar 20 IfP IfP Shock veins DaG 1051 Al Jufrah 2000 27°10.15′N 16°08.12′E 40.1 1 Shergottite 26–45 19–33 A. Bischoff, M. Horstmann, IfP and E. H. Haiderer, Vienna, Austria 8.4 IfP Anon See written description Meteorites from Mali Taoudenni Gao Dec‐2007 22°47.5′N 3°58.0′W 24370 1 Diogenite 34 69 4 2.8 A. Jambon, O. Boudouma, D. Badia, UPVI 31 UPVI AHabibi Finder— Dhamen Ouled Ali Meteorites from Mexico La Ciénega Sonora Jun‐2007 30°12′06.70N 111°56′09.14W 7632 8 H6 S3 W2 18.6 16.5 1.5 Jeff Grossman, USGS 31 SI G. Notkin Finder— G. Bruce Meteorites from northwewst Africa NWA 2151 02‐Feb‐2004 p 417.44 1 Iron, IAB‐sHL A. Rubin, UCLA 35.32 UCLA Gessler NWA 2211 Jan 2005 27690 6 L S6 W3 22.4 ± 0.4 19.1 ± 0.3 0.6 ± 0.2 K. van Drongelen, ROM ; A. E. Rubin, UCLA 85.9 UCLA ROM Melt breccia NWA 2613 1999 20.3 1 H4/5 19.1–21.1 17.1–19.3 R. Bartoschewitz, P. Appel, B. Mader, Kiel 4.7 Vernad Hochsieder NWA 2986 Morocco 2006 p 201 3 Shergottite 37.4–53.8 10.8–15.8 T. Bunch and J. Wittke 21.3 NAU Farmer, Strope See written description NWA 4802 2007 p 11.3 1 L6 S2 W1 24 20.2 1.8 A. Rubin, UCLA 2.33 UCLA Kkessel* NWA 4803 2007 p 35.5 1 L6 S4 W2 23 A. Rubin, UCLA 7.51 UCLA Kkessel* NWA 4804 2007 P 69.9 1 L4 S3 W4 22.6 14.6 2.1 A. Rubin, UCLA 14.73 UCLA Kkessel* NWA 4805 2007 p 34.5 1 L6 S3 W2 23.1 A. Rubin, UCLA 7.21 UCLA Kkessel* NWA 4861 Jul‐2005 p 2400 1 Iron, IAB complex A. Ruzicka, M. Hutson, Cascadia , S. Kissin, LHU 210.4 Cascadia Thompson NWA 5297 Morocco Mar‐2008 130 9 Primitive achondrite 28.6 A. Irving, S. Kuehner, UWS 20 UWS GHupé See written description NWA 5602 Feb‐2007 49 1 Ureilite 20.4; 9.9 17.2–17.3 7.5–7.6 A. Irving, S. Kuehner, UWS 9.8 UWS GHupé 0.33 wt% Cr 2 O 3 in ol NWA 5609 Jun‐2006 2134 1 L4 S2 W2 23.7–24.9 20.3 1.6 A. Irving, S. Kuehner, UWS 20 UWS GHupé * NWA 5691 May‐2009 259 1 Eucrite 59.1–59.6 4.6–5.1 A. Irving, S. Kuehner, UWS 22 UWS Anon NWA 5718 Algeria 2006 p 90.5 1 Shergottite 0.5–39.1 9.6 T. Bunch, J. Wittke, NAU 19.4 NAU DPitt See written description NWA 5776 Sep‐2006 p 683 1 L‐melt breccia S6 W2 22.8 ± 0.8 A. E. Rubin, UCLA 34.4 UCLA Reed NWA 5784 Morocco 2008 p 2600 1 Diogenite 31.3 T. Bunch, J. Wittke, NAU 20.6 FMNH Reed ol‐rich diogenite NWA 5787 Morocco Feb‐2009 48 1 Eucrite 48.8–49.2 4.0–4.9 A. Irving, S. Kuehner, UWS 9.6 UWS SBuhl NWA 5788 Jul‐2006 7286 1 L3.8 S2 W2 11.4–24.6 12.4–25.5; 11.7–18.7 0.6–4.6; 35.9–48.1 A. Irving, S. Kuehner, UWS 47 UWS PMani Cr 2 O 3 in ol 0.01–0.03 wt%. NWA 5935 23‐Jun‐2009 p 374 1 H5 S1 W3–4 18 16 J. Roszjar, A. Bischoff 25.1 IfP Anon NWA 5936 23‐Jun‐2009 p 235 1 H5 S2 W4 18 16 J. Roszjar, A. Bischoff 20.5 IfP Anon NWA 5939 13‐Jan‐2004 p 297 1 H3–6 S3 W2 18.3 ± 1.6 15.9 ± 1.2 J. Roszjar, A. Bischoff 20 IfP Anon NWA 5940 2‐Jul‐2009 p 151000 1 H5–6 S4 W2–3 19.5 16.5 J. Roszjar, A. Bischoff 25 IfP Anon NWA 5957 Jun‐2008 1083 1 Howardite 29.6; 63.0; 22.7–28.7 4.6; 2.6; 40.5–42.1 A. Irving, S. Kuehner, UWS 30.2 UWS Farmer FeO/MnO pyx 26.4–35.5 NWA 5959 Morocco Sep‐2009 1750 1 Howardite 24.1–27.8; 60.2; 26.2; 39.3 3.8–3.9; 1.7; 42.1; 7.5 A. Irving, S. Kuehner, UWS 20 UWS DStimpson FeO/MnO in px 25.2–32.7 Purchased in Taliouine NWA 5968 Morocco 2008 p 15.5 1 Diogenite 8.8 T. Bunch, J. Wittke, NAU 4.4 NAU Anon ol‐rich NWA 5981 Morocco Oct 2009 243 1 Lodranite 4.0; 9.7 44.4; 1.4 A. Irving, S. Kuehner, UWS 20 UWS DStimpson Paired with NWA 4478 NWA 5982 Arg Chach, Mali Mar 2009 1400 1 Eucrite, polymict 32.8; 59.4; 27.8 2.4; 4.6; 41.3 A. Irving, S. Kuehner, UWS 20 UWS Ralew FeO/MnO in pyx 32.5–34.0 NWA 6072 Morocco May 2008 p 333 3 Eucrite 64 2 R. Korotev, A. Foreman, R. Zeigler, WUSL 20.4 WUSL Labenne Augite, Fs 70 Wo 43 ; granulitic texture NWA 6074 Morocco June 2008 p 48.8 1 Diogenite 24–25 18–26 40,181 R. Korotev, A. Foreman, R. Zeigler, WUSL 10 WUSL Labenne Polymict NWA 6157 Algeria Feb‐2010 p 42 1 Diogenite, olivine 29.3–30.1 24.3 2.8 A. Irving, S. Kuehner, UWS 8.9 UWS Farmer See written description NWA 6203 Bechar, Algeria 2007 ∼30°31′N ∼4°18′W 35400 14 Iron, IAB‐MG Moderate Moderate 4.9 ± 0.2 6.9 ± 0.3 1.8 ± 0.3 C. Herd, G. Nadeau, UAb 197.9 UAb S. Buhl NWA 6235 Fezzou Village, Morocco 15‐Sep‐2005 30°55.68′N 4°51.50′W 216 1 Ureilite 4.1–22.1 3.0–19.2 0.33–10.6 Sawada a 22.05 NSMT Sawada Finder— M. Aziz NWA 6236 Fezzou Village, Morocco 4‐Oct‐2005 30°58.29′N 4°56.99′W 145 2 R4 36.0–41.6 14.5–30.5 0.31–9.7 Sawada 23.93 NSMT Sawada Meteorites from Oman Dho 1435 Zufar 5‐Feb‐2007 18°14.917′N 54°0.218′E 11.7 1 H5 S3 W3 18.6–19.9 16.4–17.1 4.91 R. Bartoschewitz, P. Appel, B. Mader, Kiel 2.34 Kiel Barto Finder— R. Bartoschewitz Dho 1445 Zufar 9‐Mar‐2003 19°26.218′N 054°42.399′E 442 1 LL5 S3 W1 31.7–32.5 25.0–26.5 3.66 R. Bartoschewitz, P. Appel, B. Mader, Kiel 20 Kiel Anon Fs 93.4 Wo 6.6 ; An 11 Or 6 Dho 1446 Zufar 9‐Mar‐2003 19°27.084′N 054°39.144′E 199 1 H5 W3 4.83 R. Bartoschewitz 20 Kiel Anon Dho 1447 Zufar 14‐Apr‐2002 18°37′N 54°11′E 49.4 3 H∼4 W5 4.62 R. Bartoschewitz 10 Kiel Anon Dho 1448 Zufar 11‐Aug‐2002 19°21′N 54°48′E 3110 Many L∼6 W4 4.32 R. Bartoschewitz 20.4 Kiel Anon Dho 1449 Zufar 11 Aug 2002 19°13.8′N 54°52.8′E 1959 Several L/LL∼6 W4 4.09 R. Bartoschewitz 21.8 Kiel Anon Dho 1450 Zufar 18‐Feb‐2008 19°15.838′N 54°43.417′E 5.4 2 LL∼6 W3 4.44 R. Bartoschewitz 1.1 Kiel Anon Dho 1451 Zufar 20‐Feb‐2008 19°12.782′N 54°37.246′E 570 3 H∼5 W4 4.65–4.81 R. Bartoschewitz 20 Kiel Anon Dho 1452 Zufar 20‐Feb‐2008 19°00.961′N 54°22.070′E 163 1 L∼6 W2 4.79 R. Bartoschewitz 20 Kiel Anon Dho 1453 Zufar 21‐Feb‐2008 18°59.919′N 54°23.629′E 402 2 L/LL∼5 W1/2 4.37–4.67 R. Bartoschewitz 20 Kiel Anon Melt pockets Dho 1455 Zufar 22‐Feb‐2008 18°58.593′N 54°24.229′E 489 6 LL5 S1 W3 31.7–32.7 25.4–25.9 3.61 R. Bartoschewitz, P. Appel, B. Mader, Kiel 20 Kiel Anon Feld An 10 Or 7 Dho 1456 Zufar 22‐Feb‐2008 18°59.278′N 54°25.095′E 90.2 1 H∼5 4.87 R. Bartoschewitz 18 Kiel Anon Melt pockets Dho 1457 Zufar 22‐Feb‐2008 18°59.905′N 54°24.974′E 11.4 1 H∼5 W4 4.94 R. Bartoschewitz 2.3 Kiel Anon Dho 1458 Zufar 22‐Feb‐2008 18°59.535′N 54°25.065′E 428 20 L∼5 W4 4.76 R. Bartoschewitz 20 Kiel Anon Dho 1459 Zufar 23‐Feb‐2008 19°01.129′N 54°22.411′E 50.4 1 H5 S1 W2 18.1–19.7 16.5–17.8 5 R. Bartoschewitz, P. Appel, B. Mader, Kiel 10.1 Kiel Anon Dho 1460 Zufar 23‐Feb‐2008 19°01.092′N 54°22.338′E 40.5 1 L∼6 W2 4.74 R. Bartoschewitz 8.1 Kiel Anon Dho 1463 Zufar 25‐Feb‐2008 18°27.167′N 54°09.693′E 23.6 1 L/LL∼4 W4 4.56 R. Bartoschewitz 4.7 Kiel Anon Dho 1464 Zufar 26‐Feb‐2008 18°34.134′N 54°10.085′E 68.5 1 H∼5 5 R. Bartoschewitz 13.7 Kiel Anon Dho 1465 Zufar 26‐Feb‐2008 18°34.143′N 54°10.268′E 237 1 L∼6 W1/2 4.78 R. Bartoschewitz 20 Kiel Anon Dho 1466 Zufar 26‐Feb‐2008 18°34.277′N 54°10.263′E 268 50 L∼6 W4 4.73 R. Bartoschewitz 20 Kiel Anon Dho 1467 Zufar 26‐Feb‐2008 18°33.969′N 54°09.477′E 1305 5 L∼5 W4 4.65 R. Bartoschewitz 20 Kiel Anon Dho 1468 Zufar 26‐Feb‐2008 18°33.969′N 54°09.477′E 65.6 1 H∼5 W4 4.94 R. Bartoschewitz 13.1 Kiel Anon Dho 1469 Zufar 26‐Feb‐2008 18°33.706′N 54°10.330′E 110 1 L∼6 W3 4.65 R. Bartoschewitz 20 Kiel Anon Dho 1470 Zufar 26‐Feb‐2008 18°34.003′N 54°10.180′E 51.6 1 H∼5 4.89 R. Bartoschewitz 10.3 Kiel Anon Melt pockets Dho 1471 Zufar 26‐Feb‐2008 18°34.001′N 54°09.623′E 760 1 H∼5 W3 4.87 R. Bartoschewitz 20 Kiel Anon Melt pockets Dho 1472 Zufar 26‐Feb‐2008 18°34.460′N 54°08.962′E 1064.1 1 LL6 S1 W1 31.1–32.2 25.8–26.2 3.63 R. Bartoschewitz, P. Appel, B. Mader, Kiel 20 Kiel Anon Feld An 10 Or 4 Dho 1473 Zufar 27‐Feb‐2008 18°36.304′N 54°10.131′E 131.2 5 L/LL∼6 W4 4.58 R. Bartoschewitz 20 Kiel Anon Dho 1475 Zufar 27‐Feb‐2008 18°36.186′N 54°10.665′E 1039.2 3 L∼6 W4 4.62 R. Bartoschewitz 20 Kiel Anon Dho 1490 Zufar 19‐Nov‐2008 18°47.870′N 54°24.262′E 309 1 H5–6 S3 W2–3 18.5 16.5 A. Bischoff, M. Matthes, M. Horstmann, IfP 27.8 IfP Anon Breccia, shock veins Dho 1491 Zufar 19‐Nov‐2008 18°44.595′N 54°22.614′E 256 1 L4–6 S4 W1 25 20 ± 2.5 A. Bischoff, M. Matthes, M. Horstmann, IfP 20.6 IfP Anon Breccia, shock veins Dho 1492 Zufar 22‐Nov‐2008 18°46.550′N 54°27.260′E 510 1 H3 S2 W4 14.5 ± 5.8 9 ± 5.5 A. Bischoff, M. Matthes, M. Horstmann, IfP 20.2 IfP Anon Dho 1493 Zufar 24‐Nov‐2008 18°40.427′N 54°27.010′E 14000 4 L6 S5 W3 22.5 19 A. Bischoff, M. Matthes, M. Horstmann, IfP 64.6 IfP Anon Shock veins Dho 1494 Zufar 25‐Nov‐2008 18°41.110′N 54°26.522′E 1400 1 H4 S2 W1–2 17.5 16 A. Bischoff, M. Matthes, M. Horstmann, IfP 33.3 IfP Anon Dho 1495 Zufar 25‐Nov‐2008 18°40.022′N 54°26.092E 2300 1 L4 S2 W1–2 22.5 18.5 A. Bischoff, M. Matthes, M. Horstmann, IfP 53.6 IfP, Univ. Muenster Anon Partly shock‐darkened Dho 1496 Zufar 25‐Nov‐2008 18°41.227′N 54°25.200′E 1000 1 LL(L)3 S3 W1–2 19 ± 10 15 ± 10 A. Bischoff, M. Matthes, M. Horstmann, IfP 37.2 IfP, Univ. Muenster Anon Dho 1497 Zufar 27‐Nov‐2008 18°43.901′N 54°23.821′E 1856 1 L3–5 S3 W0/1 23.5 ± 5.5 15 ± 6.5 A. Bischoff, M. Matthes, M. Horstmann, IfP 59.3 IfP, Univ. Muenster Anon Breccia Dho 1513 Zufar 1‐Apr‐2009 19°20′15.59N 54°31′58.54E 3782 1 L5 S2 W3 24.7–25.1 20.5 1.9 A. Irving and S. Kuehner, UWS, 20 UWS Anon Dho 1562 Zufar 16‐Jan‐2004 18°55.560′N 54°23.933′E 7550 1 L6 S3 W1 23.8 20.3 1.6 M. Ivanova, S. Borisovsky 1616 Vernad Anon Dho 1563 Zufar 9‐Dec‐2004 18°27.257′N 54°26.195′E 70 1 H5 S2 W3 18.6 16.3 1.3 M. Ivanova, S. Borisovsky 26.6 Vernad Anon Dho 1564 Zufar 8‐Dec‐2004 18°41.770′N 54°22.200′E 26 1 H5 S1 W3 17.9 15.5 1.6 M. Ivanova, S. Borisovsky 8.1 Vernad Anon Dho 1565 Zufar 2008 18°16.410′N 54°12.820 43kg many H5 S1 W3 18.7 16.5 1.3 M. Ivanova, S. Borisovsky 106.4 Vernad Anon Dho 1566 Zufar 2008 18°14.540′N 54° 6.390′E 605 1 LL5–6 S2 W2 30.5 25 2.3 M. Ivanova, S. Borisovsky 80.2 Vernad Anon Breccia JaH 349 Al Wusta 5‐Mar‐2003 19°17.879′N 055°44.996′E 64.3 1 L∼6 W4 4.59 R. Bartoschewitz 12.87 Kiel Anon JaH 350 Al Wusta 5‐Mar‐2003 19°20.338′N 055°32.682′E 67.3 1 L∼6 W3 4.76 R. Bartoschewitz 13.46 Kiel Anon JaH 351 Al Wusta 5‐Mar‐2003 19°21.721′N 055°37.021′E 437.3 8 H∼5 W4 4.89 R. Bartoschewitz 20.7 Kiel Anon JaH 352 Al Wusta 5‐Mar‐2003 19°21.620′N 055°37.668′E 1005 1 H∼6 W4 4.87 R. Bartoschewitz 22.3 Kiel Anon JaH 353 Al Wusta 5‐Mar‐2003 19°21.819′N 055°38.076′E 366.2 1 H∼5 W3 5.03 R. Bartoschewitz 20 Kiel Anon Melt rich JaH 354 Al Wusta 7‐Mar‐2003 19°21.802′N 055°38.124′E 1200.8 12 L∼6 4.66 R. Bartoschewitz 20 Kiel Anon breccia JaH 355 Al Wusta 7‐Mar‐2003 19°21.531′N 055°32.906′E 16879.1 70 L∼6 W4 4.42 R. Bartoschewitz 26.6 Kiel Anon JaH 356 Al Wusta 7‐Mar‐2003 19°21.387′N 055°31.790′E 53.3 1 H∼6 W4 4.74 R. Bartoschewitz 10.66 Kiel Anon JaH 357 Al Wusta 7‐Mar‐2003 19°21.718′N 055°36.750′E 1479.5 12 H∼6 W4 4.77 R. Bartoschewitz 20 Kiel Anon JaH 358 Al Wusta 7‐Mar‐2003 19°21.214′N 055°37.386′E 528.2 2 L∼5 W2 4.76 R. Bartoschewitz 20 Kiel Anon JaH 359 Al Wusta 9‐Mar‐2003 19°21.561′N 055°35.599′E 645.3 12 H∼4 W4 5.01 R. Bartoschewitz 21 Kiel Anon JaH 361 Al Wusta 10‐Mar‐2003 19°17.423′N 055°33.725′E 21.2 1 L∼4 4.76 R. Bartoschewitz 4.24 Kiel Anon JaH 362 Al Wusta 10‐Mar‐2003 19°20.637′N 055°44.677′E 104.5 1 L∼5 W3 4.64 R. Bartoschewitz 22.3 Kiel Anon JaH 363 Al Wusta 10‐Mar‐2003 19°33.823′N 056°03.104′E 186.5 1 H∼5 W2 5 R. Bartoschewitz 20.9 Kiel Anon JaH 364 Al Wusta 10‐Mar‐2003 19°32.732′N 056°02.618′E 735.6 1 L∼6 W4 4.32 R. Bartoschewitz 21.4 Kiel Anon JaH 365 Al Wusta 11‐Mar‐2003 19°37.119 056°02.536′E 3665.1 1 H∼4 W2 4.99 R. Bartoschewitz 20 Kiel Anon JaH 366 Al Wusta 11‐Mar‐2003 19°39.375 056°03.366′E 99.5 1 L∼6 W2 4.79 R. Bartoschewitz 22.7 Kiel Anon Melt pools JaH 367 Al Wusta 18‐Mar‐2003 19°20.737′N 055°52.304′E 572.9 12 L∼5 W5 4.47 R. Bartoschewitz 20 Kiel Anon JaH 368 Al Wusta 18‐Mar‐2003 19°16.419′N 055°48.624′E 892.7 2 H∼4 W4 4.7 R. Bartoschewitz 20.7 Kiel Anon JaH 369 Al Wusta 18‐Mar‐2003 19°17.115′N 055°49.346′E 7100 1 H∼5 W4 4.74 R. Bartoschewitz 20.4 Kiel Anon JaH 370 Al Wusta 18‐Mar‐2003 19°19.910′N 055°48.610′E 1453.1 1 L∼6 W4 4.65 R. Bartoschewitz 20 Kiel Anon JaH 371 Al Wusta 18‐Mar‐2003 19°18.617′N 055°49.855′E 660.5 9 L∼6 W4 4.66 R. Bartoschewitz 20 Kiel Anon JaH 372 Al Wusta 19‐Mar‐2003 19°21.523′N 055°42.643′E 380.9 1 H∼4 W4 5.01 R. Bartoschewitz 20 Kiel Anon JaH 373 Al Wusta 20‐Mar‐2003 19°20.328′N 055°43.117′E 68.6 8 L∼5 W4 4.69 R. Bartoschewitz 13.73 Kiel Anon JaH 374 Al Wusta 18‐Mar‐2003 19°18.160′N 055°42.223′E 60.6 4 H5 S1 W4 18.3–18.7 15.5–17.3 4.94 R. Bartoschewitz, P. Appel, B. Mader, Kiel 15.3 Kiel Anon JaH 375 Al Wusta 20‐Mar‐2003 19°18.160′N 055°42.058′E 113.4 3 L∼4 W4 4.66 R. Bartoschewitz 20 Kiel Anon JaH 376 Al Wusta 20‐Mar‐2003 19°19.104′N 055°42.182′E 1429.4 20 H5 S1 W4 17.9–18.6 15.7–17.0 4.9 R. Bartoschewitz, P. Appel, B. Mader, Kiel 21.5 Kiel Anon JaH 377 Al Wusta 21‐Mar‐2003 19°18.626′N 055°42.656′E 373.5 3 H5 S1 W4 18.2–18.8 16.3–16.9 4.92 R. Bartoschewitz, P. Appel, B. Mader, Kiel 20.3 Kiel Anon JaH 378 Al Wusta 21‐Mar‐2003 19°17.358′N 055°42.881′E 1186.3 2 L∼6 W4 4.64 R. Bartoschewitz 20.8 Kiel Anon JaH 379 Al Wusta 21‐Mar‐2003 19°17.063′N 055°42.214′E 297.7 1 H∼6 W4 4.73 R. Bartoschewitz 19.9 Kiel Anon JaH 380 Al Wusta 22‐Mar‐2003 19°18.204′N 055°42.351′E 144.5 8 H∼5 W4 4.78 R. Bartoschewitz 20 Kiel Anon JaH 381 Al Wusta 22‐Mar‐2003 19°18.448′N 055°41.869′E 501 2 H∼5 W4 4.8 R. Bartoschewitz 22.5 Kiel Anon JaH 382 Al Wusta 22‐Mar‐2003 19°17.851′N 055°46.974′E 308.9 1 H∼5 W3 4.93 R. Bartoschewitz 20.9 Kiel Anon JaH 383 Al Wusta 22‐Mar‐2003 19°16.939′N 055°46.855′E 374.8 1 H∼5 W3 4.87 R. Bartoschewitz 24.1 Kiel Anon Melt pockets JaH 384 Al Wusta 22‐Mar‐2003 19°16.859′N 055°46.991′E 519.7 2 L∼6 W4 4.66 R. Bartoschewitz 20 Kiel Anon JaH 386 Al Wusta 26‐Feb‐2003 19°17.947′N 055°47.640′E 1412.9 1 H∼5 W3 4.8 R. Bartoschewitz 20 Kiel Anon JaH 387 Al Wusta 26‐Feb‐2003 19°16.586′N 055°46.001′E 622.4 1 L5 S1 W4 25.0–26.9 20.7–22.6 4.71 R. Bartoschewitz, P. Appel, B. Mader, Kiel 20.2 Kiel Anon JaH 388 Al Wusta 26‐Feb‐2003 19°16.665′N 055°45.841′E 1589.2 1 L∼6 S1 W4 4.34 R. Bartoschewitz 21.3 Kiel Anon JaH 389 Al Wusta 23‐Feb‐2003 19°16.766′N 055°46.003′E 1059.7 1 H∼6 W4 4.9 R. Bartoschewitz 20 Kiel Anon JaH 390 Al Wusta 2‐Mar‐2003 19°16.458′N 055°45.428′E 159.2 2 H∼6 W3 4.9 R. Bartoschewitz 23.5 Kiel Anon JaH 391 Al Wusta 2‐Mar‐2003 19°16.718′N 055°46.387′E 57.9 1 H∼4 W4 5.12 R. Bartoschewitz 11.59 Kiel Anon JaH 392 Al Wusta 2‐Mar‐2003 19°17.494′N 055°47.057′E 220.8 1 H∼6 W4 4.91 R. Bartoschewitz 22.3 Kiel Anon JaH 393 Al Wusta 2‐Mar‐2003 19°19.090′N 055°46.519′E 1360.8 1 H∼5 W3 4.88 R. Bartoschewitz 20.1 Kiel Anon JaH 394 Al Wusta 3‐Mar‐2003 19°18.077′N 055°48.503′E 1174.4 1 L∼6 W4 4.45 R. Bartoschewitz 20 Kiel Anon JaH 493 Al Wusta 1‐Mar‐2007 19°47.070′N 56°25.001′E 438.7 4 L6 S3–4 W3 24.4 20.8 1.5 4.12 E. Gnos, E. Janots, B. Hofmann 438.7 NMBE NMBE Paired with JaH 494; finder—MEggimann 1 JaH 494 Al Wusta 1‐Mar‐2007 19°47.144′N 56°25.573′E 63.8 2 L6 S4 W3 26 4.12 E. Gnos, E. Janots, B. Hofmann 63.8 NMBE NMBE Paired JaH 493; finder—MEggimann 1 JaH 495 Al Wusta 06‐Mar‐2007 19°47.105′N 56°24.746′E 501.8 2 L6 S3 W4 25 4.1 E. Gnos, E. Janots, B. Hofmann 501.8 NMBE NMBE Paired JaH 493; finder—MEggimann 1 JaH 500 Al Wusta 12‐Mar‐2007 19°45.136′N 56°18.578′E 1432.2 18 H5 S2 W4 17 4.67 E. Gnos, E. Janots, B. Hofmann 1432.2 NMBE NMBE Paired JaH 501; finder—Al‐Kathiri 1 JaH 502 Al Wusta 12‐Mar‐2007 19°45.313′N 56°18.404′E 138.6 5 H5 S2 W4 19 4.95 E. Gnos, E. Janots, B. Hofmann 138.6 NMBE NMBE Paired JaH 500; finder—Al‐Kathiri 1 JaH 503 Al Wusta 12‐Mar‐2007 19°45.134′N 56°18.636′E 2421.6 27 H3–4 S2 W4 18 4.59 E. Gnos, E. Janots, B. Hofmann 2421.6 NMBE NMBE Paired JaH 500; finder—Al‐Kathiri 1 JaH 504 Al Wusta 12‐Mar‐2007 19°45.164′N 56°18.618′E 674.3 1 H3–5 S2 W4 19 4.56 E. Gnos, E. Janots, B. Hofmann 674.3 NMBE NMBE Paired JaH 500; finder—Al‐Kathiri 1 JaH 513 Zufar 20‐Jan‐2008 19°31.859′N 55°10.787′E 9.5 1 LL7 S1 W2 28.6 23.5 3.8 E. Gnos, E. Janots, B. Hofmann 9.5 NMBE NMBE See written description JaH 521 Zufar 22‐Jan‐2008 19°31.829′N 55°10.894′E 1989 113 L6 S3 W3 24.3 20.8 1.6 E. Gnos, E. Janots, B. Hofmann 1989 NMBE NMBE Paired JaH 520; finder—Al‐Kathiri 2 JaH 522 Zufar 22‐Jan‐2008 19°31.902′N 55°10.889′E 6 1 H6 18 E. Gnos, B. Hofmann 6 NMBE NMBE Paired JaH 511; finder—Al‐Kathiri 2 JaH 523 Zufar 22‐Jan‐2008 19°31.909′N 55°10.910′E 60.6 1 H6 S2 W3 19 16.7 1.4 E. Gnos, B. Hofmann 60.6 NMBE NMBE Paired JaH 511; finder—Al‐Kathiri 2 JaH 524 Zufar 22‐Jan‐2008 19°31.873′N 55°10.785′E 6 1 H6 19 E. Gnos, B. Hofmann 6 NMBE NMBE Paired JaH 511; finder—Al‐Kathiri 2 JaH 525 Zufar 22‐Jan‐2008 19°31.994′N 55°10.501′E 1.6 1 L4–6 S1 W3 24 E. Gnos, B. Hofmann 1.6 NMBE NMBE Paired JaH 511; finder—Al‐Kathiri 2 JaH 526 Zufar 22‐Jan‐2008 19°32.000′N 55°10.534′E 5.6 1 H6 19 E. Gnos, B. Hofmann 5.6 NMBE NMBE Paired JaH 511; finder—Al‐Kathiri 2 JaH 527 Zufar 22‐Jan‐2008 19°32.024′N 55°10.532′E 3.8 1 H6 18 E. Gnos, B. Hofmann 3.8 NMBE NMBE Paired JaH 511; finder—Al‐Kathiri 2 JaH 528 Zufar 22‐Jan‐2008 19°32.057′N 55°10.442′E 19.7 1 H6 S3 W4 18 E. Gnos, B. Hofmann 19.7 NMBE NMBE Paired JaH 511; finder—Al‐Kathiri 2 JaH 529 Zufar 22‐Jan‐2008 19°32.057′N 55°10.442′E 2.1 1 H6 18 E. Gnos, B. Hofmann 2.1 NMBE NMBE Paired JaH 511; finder—Al‐Kathiri 2 JaH 530 Zufar 22‐Jan‐2008 19°32.009′N 55°10.494′E 12.6 1 H4–6 S2 W4 19 E. Gnos, B. Hofmann 12.6 NMBE NMBE Paired JaH 511; finder—Al‐Kathiri 2 JaH 531 Zufar 22‐Jan‐2008 19°32.049′N 55°10.529′E 1.7 1 H6 18 E. Gnos, B. Hofmann 1.7 NMBE NMBE Paired JaH 511; finder—Al‐Kathiri 2 JaH 533 Zufar 22‐Jan‐2008 19°32.433′N 55°10.024′E 24 1 H6 S2 W4 18.1 E. Gnos, B. Hofmann 23.9 NMBE NMBE Paired JaH 511; finder—Al‐Kathiri 2 JaH 535 Zufar 22‐Jan‐2008 19°32.161′N 55°10.027′E 89.4 1 H4–6 S2 W4 18 E. Gnos, B. Hofmann 89.4 NMBE NMBE Paired JaH 511; finder—Al‐Kathiri 2 JaH 536 Zufar 22‐Jan‐2008 19°32.641′N 55°9.905′E 1 1 H6 19 E. Gnos, B. Hofmann 1 NMBE NMBE Paired JaH 511; finder—Al‐Kathiri 2 JaH 537 Zufar 22‐Jan‐2008 19°32.200′N 55°10.431′E 33.2 1 H6 S3 W4 19 E. Gnos, B. Hofmann 33.2 NMBE NMBE Paired JaH 511; finder—Al‐Kathiri 2 JaH 543 Zufar 23‐Jan‐2008 19°32.284′N 55°10.073′E 8.8 1 H6 18 E. Gnos, B. Hofmann 8.8 NMBE NMBE Paired JaH 511; finder—EGnos 2 JaH 547 Zufar 23‐Jan‐2008 19°32.292′N 55°10.100′E 105.6 1 H4–6 S2 W3 20 E. Gnos, B. Hofmann 105.6 NMBE NMBE Paired JaH 511; finder—EGnos 2 JaH 551 Zufar 23‐Jan‐2008 19°31.748′N 55°10.899′E 24 1 H4–6 S2 W3 18.1 E. Gnos, B. Hofmann 23.9 NMBE NMBE paired JaH 511; finder—EGnos 1 JaH 559 Al Wusta 25‐Jan‐2008 19°50.395′N 56°6.310′E 208.6 8 H3.7/3.8 S2 W4 18.6–20.6 14.6–19.9 0.2–2.1 E. Gnos, B. Hofmann 208.6 NMBE NMBE Paired JaH 560; chondrule size 0.35 mm, bulk Fe 24.1%; finder—EGnos 1 SaU 438 Al Wusta 11‐Feb‐2007 21°5.943′N 57°16.060′E 90.7 1 H5 S4 W2 19.6–20.3 17.1–18.0 5.04 R. Bartoschewitz, P. Appel, B. Mader, Kiel 18.2 Kiel Barto Finder—C. Bartoschewitz SaU 463 Al Wusta 28‐Feb‐2008 20°00.951′N 56°33.483′E 519.3 2 L∼6 4.72 R. Bartoschewitz 20 Kiel Anon Petrologic type is approximate. SaU 464 Al Wusta 29‐Feb‐2008 20°01.534′N 56°33.496′E 210.3 1 LL5 S1 W1 27.3–28.4 7.3–24.8 3.81 R. Bartoschewitz, P. Appel, B. Mader, Kiel 20 Kiel Anon An 24 Or 17 SaU 465 Al Wusta 29‐Feb‐2008 20°00.816′N 56°33.472′E 100.5 1 H∼6 W4 4.91 R. Bartoschewitz 20 Kiel Anon SaU 466 Al Wusta 29 Feb 2008 20°05.820′N 56°37.468′E 228.3 2 L/LL∼5 W4 4.48 R. Bartoschewitz 20 Kiel Anon SaU 467 Al Wusta 22‐Feb‐2008 20°09.599′N 56°38.775′E 271.7 1 L∼5 W2 4.7 R. Bartoschewitz 20 Kiel Anon SaU 468 Al Wusta 12‐Mar‐2003 20°59.869′N 057°17.697′E 59.8 1 H∼6 W4 4.74 R. Bartoschewitz 11.96 Kiel Anon SaU 469 Al Wusta 12‐Mar‐2003 20°59.784′N 057°17.272′E 365.5 5 L∼6 W2/3 4.61 R. Bartoschewitz 20 Kiel Anon Shişr 113 Zufar 3‐Feb‐2007 18°15.057′N 53°59.921′E 12.5 1 H∼5 W4 4.86 R. Bartoschewitz 2.7 Kiel Barto Finder— C. Bartoschewitz Shişr 114 Zufar 3‐Feb‐2007 18°15.171′N 53°59.92′E 2.4 1 H∼5 W4 4.92 R. Bartoschewitz 0.48 Kiel Barto Finder— C. Bartoschewitz Shişr 115 Zufar 3‐Feb‐2007 18°15.224′N 53°59.925′E 2.9 1 H∼5 W4 4.95 R. Bartoschewitz 0.48 Kiel Barto Finder— C. Bartoschewitz Shişr 116 Zufar 3‐Feb‐2007 18°15.225′N 53°59.918′E 2.9 1 H∼5 W4 4.85 R. Bartoschewitz 0.58 Kiel Barto Finder— C. Bartoschewitz Shişr 117 Zufar 3‐Feb‐2007 18°15.263′N 53°59.903′E 4.8 1 H∼5 W4 4.86 R. Bartoschewitz 1.1 Kiel Barto Finder— C. Bartoschewitz Shişr 118 Zufar 03 Feb 2007 18°15.183′N 53°59.731′E 10.2 1 L/LL4 W2 24.6–27.9 20.8–22.8 4.75 R. Bartoschewitz, P. Appel, B. Mader, Kiel 2.04 Kiel Barto An 11 Or 3‐5 ; kamacite Co 0.9%; finder—C. Bartoschewitz Shişr 119 Zufar 3‐Feb‐2007 18°15.254′N 53°59.88′E 6.8 1 H∼5 W4 4.8 R. Bartoschewitz 1.36 Kiel Barto Finder— C. Bartoschewitz Shişr 120 Zufar 4‐Feb‐2007 18°15.279′N 53°59.668′E 8.2 2 H∼5 W4 4.92 R. Bartoschewitz 1.64 Kiel Barto Finder— C. Bartoschewitz Shişr 121 Zufar 4‐Feb‐2007 18°15.517′N 53°59.528′E 49 2 H4 S2 W2 18.8–19.6 16.2–17.2 4.89 R. Bartoschewitz, P. Appel, B. Mader, Kiel 9.8 Kiel Barto Finder— C. Bartoschewitz Shişr 122 Zufar 4‐Feb‐2007 18°15.524′N 53°59.592′E 46.2 1 H∼5 W3 4.84 R. Bartoschewitz 9.24 Kiel Barto Finder— C. Bartoschewitz Shişr 123 Zufar 4‐Feb‐2007 18°15.523′N 53°59.592′E 48.2 1 H∼5 W1 4.94 R. Bartoschewitz 9.64 Kiel Barto Finder— C. Bartoschewitz Shişr 124 Zufar 4‐Feb‐2007 18°15.521′N 53°59.594′E 1.9 1 H∼5 W4 4.78 R. Bartoschewitz 0.38 Kiel Barto Finder— C. Bartoschewitz Shişr 126 Zufar 4‐Feb‐2007 18°15.477′N 53°59.605′E 11.7 1 H5 S2 W3 18.2–20.5 16.2–17.2 4.62 R. Bartoschewitz, P. Appel, B. Mader, Kiel 2.34 Kiel Barto Finder— C. Bartoschewitz Shişr 127 Zufar 4‐Feb‐2007 18°15.483′N 53°59.591′E 6.1 1 H∼5 W2 4.85 R. Bartoschewitz 1.22 Kiel Barto Finder— C. Bartoschewitz Shişr 128 Zufar 4‐Feb‐2007 18°15.488′N 53°59.59′E 52.4 1 H∼5 W3 4.76 R. Bartoschewitz 11.7 Kiel Barto Finder— C. Bartoschewitz Shişr 129 Zufar 4‐Feb‐2007 18°15.481′N 53°59.608′E 25.2 1 H∼5 W4 4.78 R. Bartoschewitz 5.04 Kiel Barto Finder— C. Bartoschewitz Shişr 130 Zufar 4‐Feb‐2007 18°15.491′N 53°59.588′E 13.4 1 H∼5 W4 4.87 R. Bartoschewitz 3.1 Kiel Barto Finder— C. Bartoschewitz Shişr 131 Zufar 4‐Feb‐2007 18°15.503′N 53°59.569′E 2.8 1 H∼5 W4 4.84 R. Bartoschewitz 0.56 Kiel Barto Finder— C. Bartoschewitz Shişr 132 Zufar 4‐Feb‐2007 18°15.525′N 53°59.547′E 13.6 1 H∼5 W1 4.96 R. Bartoschewitz 3.3 Kiel Barto Finder— C. Bartoschewitz Shişr 133 Zufar 4‐Feb‐2007 18°15.565′N 53°59.579′E 12.3 1 H∼5 W4 4.92 R. Bartoschewitz 2.46 Kiel Barto Finder— C. Bartoschewitz Shişr 134 Zufar 5‐Feb‐2007 18°15.53′N 53°59.571′E 0.5 1 H∼5 W4 4.71 R. Bartoschewitz 0.16 Kiel Barto Finder— C. Bartoschewitz Shişr 135 Zufar 5‐Feb‐2007 18°15.541′N 53°59.506′E 69.7 1 H∼5 W3 4.77 R. Bartoschewitz 13.94 Kiel Barto Finder— C. Bartoschewitz Shişr 141 Zufar 3‐Feb‐2007 18°15.232′N 53°59.87′E 38.6 2 H∼5 W2 4.94 R. Bartoschewitz 9.2 Kiel Barto Finder— R. Bartoschewitz Shişr 142 Zufar 3‐Feb‐2007 18°15.088′N 53°59.931′E 25.3 1 H∼5 W3 4.82 R. Bartoschewitz 5.06 Kiel Barto Finder— R. Bartoschewitz Shişr 143 Zufar 3‐Feb‐2007 18°15.087′N 53°59.816′E 16 1 H∼5 W4 4.83 R. Bartoschewitz 4.3 Kiel Barto Finder— R. Bartoschewitz Shişr 145 Zufar 4‐Feb‐2007 18°15.133′N 53°59.877′E 12.7 1 H∼5 W4 4.82 R. Bartoschewitz 2.54 Kiel Barto Finder— R. Bartoschewitz Shişr 146 Zufar 4‐Feb‐2007 18°15.113′N 53°59.88′E 6.9 1 H∼5 W4 4.88 R. Bartoschewitz 1.8 Kiel Barto Finder— R. Bartoschewitz Shişr 147 Zufar 4‐Feb‐2007 18°15.052′N 53°59.817′E 20.7 1 H∼5 W3 4.85 R. Bartoschewitz 4.14 Kiel Barto Finder— R. Bartoschewitz Shişr 148 Zufar 4‐Feb‐2007 18°15.043′N 53°59.8′E 23 2 H∼5 W3 4.92 R. Bartoschewitz 4.5 Kiel Barto Finder— R. Bartoschewitz Shişr 149 Zufar 4‐Feb‐2007 18°15.13′N 53°59.842′E 14.1 1 H∼5 W4 4.77 R. Bartoschewitz 2.82 Kiel Barto Finder— R. Bartoschewitz Shişr 150 Zufar 4‐Feb‐2007 18°15.239′N 53°59.713′E 61.3 1 H∼5 W2 4.87 R. Bartoschewitz 12.4 Kiel Barto Finder— R. Bartoschewitz Shişr 151 Zufar 4‐Feb‐2007 18°15.254′N 53°59.691′E 8.1 1 H∼5 W2 4.8 R. Bartoschewitz 1.62 Kiel Barto Finder— R. Bartoschewitz Shişr 152 Zufar 4‐Feb‐2007 18°15.312′N 53°59.822′E 12.8 2 H∼5 W3 4.92 R. Bartoschewitz 2.9 Kiel Barto Finder— R. Bartoschewitz Shişr 153 Zufar 4‐Feb‐2007 18°15.259′N 53°59.73′E 9.8 1 H∼5 W2 4.93 R. Bartoschewitz 1.96 Kiel Barto Finder— R. Bartoschewitz Shişr 154 Zufar 4‐Feb‐2007 18°15.537′N 53°59.624′E 53.2 1 H∼5 W4 4.87 R. Bartoschewitz 10.8 Kiel Barto Finder— R. Bartoschewitz Shişr 155 Zufar 5‐Feb‐2007 18°15.591′N 53°59.569′E 32.5 1 H4 S2 W3 18.9–19.8 16.5–19.4 4.83 R. Bartoschewitz, P. Appel, B. Mader, Kiel 6.7 Kiel Barto Finder— R. Bartoschewitz Shişr 156 Zufar 5‐Feb‐2007 18°15.666′N 53°59.599′E 130 1 H∼5 W4 4.86 R. Bartoschewitz 20 Kiel Barto Finder— R. Bartoschewitz Shişr 157 Zufar 5‐Feb‐2007 18°15.663′N 53°59.54′E 5.6 1 H∼5 W3 4.89 R. Bartoschewitz 1.12 Kiel Barto Finder— R. Bartoschewitz Shişr 166 Zufar 10‐Apr‐2008 18°32′56.68N 53°58′40.73E 128.8 1 Lunar 39 50 27 R. Zeigler and R. Korotev 20.1 WUSL Labenne* See written description Meteorites from Romania Pleşcoi Plescoi Village, Berca Commune, Buzau Co 12‐Jun‐2008 45°16′30″N 26°42′35″E 6913 1 L5–6 S2 W1 25.5 ± 0.3 21.4 ± 0.1 1.3 ± 0.2 D. Pop and G. Benedix 20 BBU M. Popescu* See written description Meteorites from Russia Batyushkovo Smolensk Region Jun‐2007 55°32.92′N 35°17.97′E 4620 1 L5 S5 W1 23.7 20.1 1.6 D.D. Badjukov, Vernad 4620 Vernad Vernad Kirishi Leningrad Region Sep‐2006 59°32.9′N 32°06.8′E 1350 1 L4 S1 W0 24.5 13.8 D.D. Badjukov, Vernad 46.5 Vernad Belov pyx: Fs 2‐26 Meteorites from Saudi Arabia AaU 001 Ash Sharqiyah 20‐Mar‐2008 22°43.315′N 48°57.562′E 194.3 1 H3.8 S2 W2/3 17.6–20.1 17.3–21.6 0.6–2.5 E. Gnos, B. Hofmann 20.5 MHNGE SGS Mean chondrule size 0.32 mm, bulk Fe 24.8 wt%, finder—EGnos 1 Qulumat Nadqan 001 Ash Sharqiyah 21‐Mar‐2008 23°8.581′N 49°31.951′E 13901 6 L3.7 S3 W1 18.9–27.6 16.8–21.2 0.2–2.1 E. Gnos, B. Hofmann 36 MHNGE SGS mean chondrule size 0.60 mm, bulk Fe 20.5 wt%; finder—EGnos 1 Yabrin 001 Ash Sharqiyah 19‐Mar‐2008 23°20.865′N 48°44.245′E 65.193 1 LL5 S4 W2 26.4 22 1.5 E. Gnos, B. Hofmann 15 MHNGE SGS Ringwoodite, mean chondrule size 1.0 mm, bulk Fe 19.7 wt%; finder—EGnos 1 Yabrin 002 Ash Sharqiyah 19‐Mar‐2008 23°21.430′N 48°43.347′E 46.324 1 H5 S2 W2 18.2 15.9 1.1 E. Gnos, B. Hofmann 10 MHNGE SGS Mean chondrule size 0.41 mm, bulk Fe 24.5 wt%; finder—EGnos 1 Meteorites from Slovenia Jesenice Upper Sava Valley 9‐Apr‐2009 46°25.282′N 14°03.130′E 3667 3 L6 S3 W0/1 25 21 A. Bischoff 3300 SMNH SMNH See written description Meteorites from Tunisia En Naffatiyah Madaniyin 20‐Mar‐2007 33°13.133′N 10°50.067′E 87.2 1 L6 S4 W2–3 25.5 21 Addi Bischoff 19 IFP Anon Synonym: Neffatia Tieret 001 Tieret 22‐Feb‐2009 30°44′53.5″N 10°12′36.6″E 602 1 H6 S1 W2 18.2 15.9 1.7 4.89 L. Folco 8.8 MNA‐SI Tunis See written description Tieret